The baby-sitters club. 2, The truth about Stacey - Telgemeier, Raina; Martin, Ann M., 1955- (New York : Graphix, 2006)
A graphic novel adaptation in which Stacey's move to a new town and her struggle with diabetes are made easier by her friendships with Kristy, Claudia, and Mary Anne, and her participation as a member of the Baby-sitter's Club.
Based on: The truth about Stacey / Ann M. Martin.
3-6
3.1
Keywords: Friendship -- Comic books, strips, etc -- Fiction; Clubs -- Comic books, strips, etc -- Fiction; Diabetes -- Comic books, strips, etc -- Fiction; Babysitters -- Comic books, strips, etc -- Fiction; Graphic novels; Friendship -- Juvenile fiction; Clubs -- Juvenile fiction; Diabetes -- Juvenile fiction; Babysitters -- Juvenile fiction; Graphic novels; Graphic novel adaptations; Comics (Graphic works)